2020
DOI: 10.24057/2071-9388-2019-165
|View full text |Cite
|
Sign up to set email alerts
|

Moving Beyond Economic Analysis: Assessing The Socio-Cultural Impacts Of Displacement And Resettlement By Sardar Sarovar Project, India

Abstract: The  large scale development  projects like dams have been  justified for a greater economic  benefit of the nation. However, the development projects have become synonymous with land acquisition leading to dispossession and forced migration of a large number of people and their involuntary resettlement. Unfortunately, too much focus on the economic benefits of such large scale projects has omitted many relevant tangible and intangible socio-cultural aspects and ignored the impacts of development policies that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…We contend that gender and socioeconomic inequality outcomes have been significantly influenced by the reality of power, allowing men to reinvent their masculinity to perpetuate stereotypes of male superiority and female servitude (Sikka, 2020;Sikka & Carol, 2021;Sikka & Mathur, 2018). In none of the above situations did women have decision-making powers when it came to project planning or negotiations.…”
Section: Decision-making Capacity Is Lostmentioning
confidence: 98%
See 2 more Smart Citations
“…We contend that gender and socioeconomic inequality outcomes have been significantly influenced by the reality of power, allowing men to reinvent their masculinity to perpetuate stereotypes of male superiority and female servitude (Sikka, 2020;Sikka & Carol, 2021;Sikka & Mathur, 2018). In none of the above situations did women have decision-making powers when it came to project planning or negotiations.…”
Section: Decision-making Capacity Is Lostmentioning
confidence: 98%
“…Our systematic review revealed this to be one of the main categories. A small body of research (Mehta, 2009;Sikka, 2018Sikka, , 2020Sikka & Carol, 2021) has been done to identify gender differences in resilience.…”
Section: Dams and Hydropower Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, dam projects have been envisaged as icons of development due to the criticality of hydroelectricity, oods control and reservoirs for agricultural activities (Global Water Partnership, 2016; Isaacman & Musemwa, 2021). However, rapid technological and engineering interventions designed for watershed development projects or hydropower production facilities have become synonymous with compulsory land acquisition, forest degradation, and inundation of aquatic ecosystems (Beck et al, 2012;Bunn, 2016;Obour et al, 2016;Sikka, 2020). However, several African countries continue to approve such projects without fully addressing the consequences of developing dams or 'grey' infrastructures on affected ecosystems in the 21st century.…”
Section: Introductionmentioning
confidence: 99%
“…Both the development and disaster-induced resettlement literature show some evidence of improved physical assets, such as housing and some basic infrastructure (Vickery 2017;Li and Song 2009), with adverse effects related to loss of livelihood resources and impoverishment (Nikuze et al 2019;Mteki et al 2017;Patel et al 2015;Cernea 1997). Recent studies have also identified social-cultural impacts such as changes in dress patterns and marriage customs, the loss of tribal folk art, the destruction of social networks, and increased violence resulting from developmentinduced displacement (Sikka 2020). Arnall (2019) and Rew et al (2006) have cautioned that developmental relocations are challenging to achieve in practice due to the operational complexities of resettlement policies both in terms of developing coherent policy and achieving effective implementation on the ground.…”
Section: Introductionmentioning
confidence: 99%